Systematic analysis of fractured specimens of composite laminates: Different perspectives between tensile, flexural, Mode I, and Mode II test - Muflikhun, Muhammad Akhsin; Yokozeki, Tomohiro (KeAi Publishing Communications Ltd., 2023)
Novel hybrid laminates consisting of carbon fiber-reinforced polymers and steel plate cold commercial (CFRP-SPCC) have been successfully manufactured and tested in the present study. Four different tests have been made i.e., tensile test, flexural test, double cantilever beam (DCB) or Mode I test, and end notched flexure (ENF) or Mode II test. After being tested, these samples need to be evaluated. Hence, an inappropriate evaluation step while identifying the cause of failure of the failed specimens can create a false conclusion. The present study aims to systematically evaluate the fractured specimens of CFRP-SPCC in different tests (tensile, flexural, DCB, and ENF test) using different tools, i.e., pocket camera, digital microscope, light microscope, and Scanning Electron Microscopy (SEM). The results showed, in terms of tensile, the highest strength occurred with 1475.4 MPa. In comparison, the highest flexural strength occurred with 1516.1 MPa, while DCB and ENF showed the highest values with 116.4 and 330 J/m2, respectively. Furthermore, the results showed that digital and light microscopes are satisfied to evaluate the specimen in tensile test. However, for the flexural test, ENF, and DCB test, besides the light microscope, further analysis using SEM-EDX is recommended to evaluate the specimen after failure.